Մարմնազննական (ֆիզիոգնոմիկական) երկերը Մատենադարանի ձեռագրերում - Մոսիկյան, Կարինե (Մատենադարան)
The article analyzes the mediaeval perceptions of physiognomy. Physiognomy establishes connection between the inborn signs of the human body (facial features, shape of head, ears, eyes, legs and specific features of the structure of other parts of the body) and character, temperament. The sources of this knowledge are in the medical science with which it was connected directly or indirectly during the whole period of its development. Several works related to this subject are found in manuscripts kept in Matenadaran, mainly translated into Classical Armenian from Latin in the 17th–18th centuries. The largest of them is the Armenian version of the book of Giambattista Della Porta on human physiognomy: De physiognomia humana, abridged by Francesco Stelluti. The second lengthy work is a section from Albert the Great’s somatoscopy. We are planning to publish Giambattista Della Porta’s work on the basis of the Armenian manuscripts kept in Matenadaran. В статье проанализированы средневековые представления о физиогномике. Физиогномика устанавливает связи между врожденными элементами структуры тела (черты лица, форма головы, особенности строения ушей, глаз, ног и т. д.) со свойствами характера и темперамента человека. Истоки физиогномики следует искать в медицине, с которой прямо или косвенно она была связана на всем протяжении своего развития. Рукописи Матенадарана содержат несколько произведений, посвященных этому предмету – по большей части переведенные с латыни на древнеармянский в 17–18 вв. Самое объемное из них – книга Джамбаттиста делла Порте «Физиогномика человека» (перевод сделан с сокращенной версии Франческо Стеллути). Второе по объему произведение – отрывок из книги Альберта Великого «Сумма Богословия». Мы намерены издать трактат делла Порта на основе хранящихся в Матенадаране рукописей.
Keywords: Բնագիտություն